Mobile learning en la enseñanza aprendizaje de las ciencias naturales en el décimo año de educación general básica - Nieto Cuenca, Marco Vinicio (Machala, 2022)
The current research project is entitled mobile learning in the teaching and learning of natural sciences in tenth year of general basic education, which was carried out in the Educational Institution "Alberto Cruz Murillo" located in the city of Machala belonging to the province of El Oro, we were hosted by ING. Betzy Beatris Olarte Pambi of the subject of Natural Sciences and the pleasant support of the students of the tenth year of basic parallel "A". In the field of education, this emergency has led to the massive closure of face-to-face activities of educational institutions in more than 190 countries in order to prevent the spread of the virus and mitigate its impact. In the field of education, most of the measures taken by countries in the region in response to the crisis have involved the suspension of face-to-face classes at all levels of education, which has led to three main lines of action: the implementation of distance education modalities, using a variety of formats and platforms (with or without the use of technology); support and mobilization of staff and the educational community; and concern for the health and well-being of students. It should be reiterated that, given this new situation, it is necessary to have teachers trained in the technology era to be able to respond to the various changes and use technology to support the teaching and learning process of students, since students must be involved in the development of new skills and capabilities and become updated professionals in the new digital era. Therefore, the main objective of the study is the use of M-Learning as a support tool for the ASP of the subject of natural sciences in students to help them improve their skills and academic performance. It is worth mentioning that it was carried out with a quantitative and qualitative approach (interview and survey) and worked with the participation of 38 students, 23 boys and 15 girls between 14 and 15 years of age of the tenth year of basic education and the teacher of the subject of Natural Sciences. Moving forward, it is worth mentioning that for the development of this prototype we used the MADAMDM approach, a flexible method for the design of multimedia applications for mobile devices, which allowed us to achieve a correct structure in my prototype. Finally, it is a great pleasure to mention that very favorable and satisfactory results have been obtained through analysis and results, these effective responses and demonstrations have been obtained and congratulations for its successful completion and the creation of the educational mobile application "CCNN".
El actual proyecto de investigación está titulado mobile learning en la enseñanza aprendizaje de las ciencias naturales en décimo año de educación general básica, el cual se llevó a cabo en la Institución Educativa “Alberto Cruz Murillo” ubicado en la ciudad de Machala perteneciente a la provincia de El Oro, mantuvimos la acogida de la ING. Betzy Beatris Olarte Pambi de la asignatura de Ciencias Naturales y el grato apoyo de los estudiantes del décimo año de básica paralelo “A”. En la esfera de la educación, esta emergencia ha dado lugar al cierre masivo de las actividades presenciales de instituciones educativas en más de 190 países con el fin de evitar la propagación del virus y mitigar su impacto. En el ámbito educativo, la mayoría de las medidas que han tomado los países de la región frente a la crisis han implicado la suspensión de las clases presenciales en todos los niveles educativos, lo que ha llevado a nacer en tres ejes principales. acción: la implementación de modalidades de educación a distancia, mediante el uso de una variedad de formatos y plataformas (con o sin uso de tecnología); apoyo y movilización del personal y de la comunidad educativa, y preocupación por la salud y el bienestar de los estudiantes. Cabe reiterar que, ante esta nueva situación, es necesario contar con docentes formados en la era de la tecnología para poder responder a los diversos cambios y utilizar la tecnología para apoyar el proceso de enseñanza y aprendizaje de los estudiantes, ya que los estudiantes deben involucrarse en el desarrollo nuevas habilidades y capacidades y convertirse en profesionales actualizados en la nueva era digital. Por lo tanto, el objetivo principal del estudio es el uso del M-Learning como herramienta de apoyo para el PEA de la materia de ciencias naturales en los estudiantes para ayudarlos a mejorar sus habilidades y desempeño académico. Cabe mencionar que se llevó acabo el un enfoque cuantitativo y cualitativo (entrevista y encuesta) y se trabajó con una participación de 38 estudiantes, 23 varones y 15 mujeres de entre 14 y 15 años de edad del décimo año de educación básica y el docente de la asignatura de Ciencias Naturales. Avanzando, cabe mencionar que para el desarrollo de este prototipo se utilizó el enfoque MADAMDM, un método flexible para el diseño de aplicaciones multimedia para dispositivos móviles, lo que nos permitió lograr una estructura correcta en mi prototipo. Finalmente, es un gran placer mencionar que se han obtenido resultados muy favorables y satisfactorios a través del análisis y los resultados, se han obtenido estas respuestas y demostraciones efectivas y felicitaciones por su exitosa culminación y la creación de la aplicación móvil educativa “CCNN”.
Keywords: APLICACION EDUCATIVA; NUEVA TECNOLOGIA; ERA DIGITAL